Ophthalmic Intervention of Naringenin Decreases Vascular Endothelial Growth Factor by Counteracting Oxidative Stress and Cellular Damage in In Vivo Zebrafish - Gokul Sudhakaran; Abhirami Chandran; A. R. Sreekutty; S. Madesh; Raman Pachaiappan; Bader O. Almutairi; Selvaraj Arokiyaraj; Zulhisyam Abdul Kari; Guillermo Tellez-Isaias; Ajay Guru; Jesu Arockiaraj (Molecules, 2023)
Diabetes Mellitus is a metabolic disease that leads to microvascular complications like Diabetic retinopathy (DR), a major cause of blindness worldwide. Current medications for DR are expensive and report multiple side effects; therefore, an alternative medication that alleviates the disease condition is required. An interventional approach targeting the vascular endothelial growth factor (VEGF) remains a treatment strategy for DR. Anti-VEGF medicines are being investigated as the main therapy for managing vision-threatening complications of DR, such as diabetic macular oedema. Therefore, this study investigated the effect of flavonoid naringenin (NG) from citrus fruits on inhibiting early DR in zebrafish. When exposed to 130 mM glucose, the zebrafish larvae developed a hyperglycaemic condition accompanied by oxidative stress, cellular damage, and lipid peroxidation. Similarly, when adult zebrafish were exposed to 4% Glucose, high glucose levels were observed in the ocular region and massive destruction in the retinal membrane. High glucose upregulated the expression of VEGF. In comparison, the co-exposure to NG inhibited oxidative stress and cellular damage and restored the glutathione levels in the ocular region of the zebrafish larvae. NG regressed the glucose levels and cellular damage along with an inhibition of macular degeneration in the retina of adult zebrafish and normalized the overexpression of VEGF as a promising strategy for treating DR. Therefore, intervention of NG could alleviate the domestication of alternative medicine in ophthalmic research.